Self‐Efficacy and Motivation to Quit Marijuana Use among Young Women. (25th June 2013) - Caviness, Celeste M.; Hagerty, Claire E.; Anderson, Bradley J.; de Dios, Marcel A.; Hayaki, Jumi; Herman, Debra; Stein, Michael D.
<x xml:space="preserve">Abstract</x> Background and Objectives Assessing motivation to quit substance use is recommended as part of brief interventions. The purpose of this study was to determine correlates of desire to quit marijuana use among young adult women enrolled in a brief motivational intervention trial. Methods Participants were 332 female marijuana users, aged 18–24, who rated their current desire to quit using a single item change ladder. We hypothesized self‐efficacy and prior quit attempts will interact in this population to increase motivation to quit. Results Participants had a mean age of 20.5 years, 67.7% were non‐Hispanic Caucasian, and 60% had some desire to quit marijuana use. Using multivariate linear regression, quit desire was significantly lower among Caucasians (b = −.256; 95% CI −.489; −.037) and more frequent marijuana users (b = −.268; 95% CI −.372; −.166), and higher among those with previous quit attempts (b = .454; 95% CI .235; .671), and greater marijuana problem severity (b = .408; 95% CI .302; .514). Greater refusal self‐efficacy was associated with greater quit desire among participants with previous quit attempts, but not among those without prior quit attempts (b = .241; 95% CI .050; .440). Conclusions and Scientific Significance Understanding the factors relating to quit desire among marijuana users may allow clinicians to tailor counseling so as to increase readiness to quit and decrease use and its associated consequences. (Am J Addict 2013;22:373–380)